Evaluation of long-term safety profile of an EU-GMP certified Cannabis sativa L. strain in a naturally aging preclinical model - Stanciu, Gabriela-Dumitrita; Costachescu, Ivona; Ababei, Daniela-Carmen; Szilagyi, Andrei; Gogu, Raluca-Maria; Craciun, Vlad-Constantin; Timofte, Andrei-Daniel; Caruntu, Irina-Draga; Dobre, Cristina-Elena; Tamba, Bogdan-Ionel (Frontiers in Pharmacology, 2025)
Aging is characterized in part by chronic, low-grade inflammation, a major driver of cognitive decline, metabolic imbalance and organ dysfunction. Despite its central role in age-related morbidity, pharmacological strategies with well-defined long-term safety profiles remain limited. Phytocannabinoids have been proposed as modulators of neuroinflammatory and metabolic pathways, but their chronic safety during natural aging is poorly characterized. Our team has previously reported the acute and 28-day repeated-dose toxicity profile of an EU-GMP certified Cannabis sativa L. strain (Cannabixir® Medium Flos). Here, we extend this work by assessing its long-term safety in a naturally aging preclinical model. Mature to older mice received chronic, intermittent administration of Cannabixir® Medium Flos (2.5, 5, and 10 mg/kg), defined as daily weekday dosing for 3 or 6 months. Clinical and histopathological evaluations were conducted with a focus on systemic and central nervous system safety. Chronic administration was well tolerated across all doses and durations. Body weight remained stable despite increased food intake. Respiratory quotient values were preserved and close to 1 across all groups. Histological analyses confirmed preserved neuronal and glial architecture with no evidence of central nervous system injury or other organ-level toxicity. Long-term, intermittent Cannabixir® Medium Flos administration was well tolerated in naturally aged mice, with no adverse effects on systemic physiology or central nervous system integrity. Together with prior acute and sub-chronic toxicity data, these findings provide robust evidence supporting the long-term safety of EU-GMP certified Cannabis sativa L. strain in the context of aging.